Sustainability Strategy in Transforming Revolving Fund Management: Case Study of the Ex-National Program for Independent Community Empowerment Rural in Tuban Regency - Eko Wardono; Asmorowati, Sulikah; Suaedi, Falih; Setijaningrum, Erna (Journal of Governance and Administrative Reform, 2024)
Abstract After the conclusion of the National Program for Community Empowerment in 2015, Tuban Regency took the initiative to establish Regent Regulation Number 27 of 2018 to manage the remaining assets, including revolving funds. This research aims to describe and analyze the sustainability strategies for managing the revolving funds from the National Program for Community Empowerment in Rural Areas (PNPM-MPd) in Tuban Regency. The focus is on the sustainability theory by Aras & Crowther (2008), encompassing societal influence, environmental impact, organizational culture, and finance. This qualitative descriptive study involved 12 informants. Findings indicate that Rengel and Semanding Sub-districts successfully implemented societal influence through strategies like collateral-free capital access, social funds, and the leadership of group leaders. Environmental impact was addressed through financing strategies for farmers and agreements to defer payments during crop failures. Financial aspects were evident in the increased assets of BUMDesma, innovative strategies by BUMDesma administrators, and transparency and accountability in revolving fund management. However, the organizational culture aspect was not optimally implemented due to a lack of coordination and synergy between regional device organizations (OPD) or the district guidance team, and passive and subjective village leadership.  Keywords: continuity; community empowerment; BUMDes Together     Abstrak  Setelah berakhirnya Program Nasional Pemberdayaan Masyarakat pada tahun 2015, Kabupaten Tuban berinisiatif menetapkan Peraturan Bupati Tuban Nomor 27 Tahun 2018 untuk mengelola aset-aset yang ditinggalkan, termasuk dana bergulir. Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis strategi keberlanjutan pengelolaan dana bergulir eks Program Nasional Pemberdayaan Masyarakat Mandiri-Perdesaan (PNPM-MPd) di Kabupaten Tuban, dengan berfokus pada teori sustainability oleh Aras & Crowther (2008) yang mencakup aspek societal influence, environmental impact, organisational culture, dan finance. Penelitian ini menggunakan metode deskriptif kualitatif dan melibatkan 12 informan. Temuan menunjukkan bahwa Kecamatan Rengel dan Semanding telah berhasil menerapkan aspek societal influence melalui strategi akses permodalan tanpa agunan, dana sosial, dan ketokohan ketua kelompok. Aspek environmental impact diwujudkan melalui strategi permodalan bagi petani dan kesepakatan penangguhan pembayaran saat gagal panen. Aspek finance ditunjukkan melalui peningkatan aset BUMDesma, strategi inovatif pengurus BUMDesma, serta transparansi dan akuntabilitas dalam pengelolaan dana bergulir. Namun, aspek organisational culture masih belum diterapkan secara optimal, karena tidak adanya koordinasi dan sinergi antar Organisasi Perangkat Daerah (OPD) atau tim pembina kabupaten dan kepemimpinan kepala desa yang pasif dan subjektif. Kata kunci: keberlanjutan; pemberdayaan masyarakat; BUMDes bersama.